Response of french bean (Phaseolus vulgaris L.) to rate and ratio of potassium fertilizer application - U. R., Sangakkara (Universiti Putra Malaysia Press, 1996)
A field study was undertaken to evaluate the effect of potassium fertilizer, when applied in different ratios, as a basal or top dressing on vegetative growth, immature pod and seed yield of French bean as well as seed quality for planting purpose determined by germination before and after controlled deterioration. The ratios of fertilizer application at a given rate of 100:0,50: or 0:100, were added at planting (basal) or at flowering (R1 stage - top dressing). Establishment of French bean was not affected by potassium. In contrast, vegetative growth and most yield components increased significantly with up to 100 kg K20 per ha. Application of a given rate only at planting (100:0) enhanced vegetative growth compared with a split rate. Application at flowering alone (0: 100) reduced all measured parameters, confirming the requirement of potassium at planting. Yields of immature pods harvested for vegetable purposes were not significantly increased by the two applications in the ratio of 50:50 (basal: top dressing). Seed quality determined by germination before and after controlled deterioration was also affected and split applications of 100 kg K20 in the ratio of 50:50 increased germinability.